The Deterioration of Reproduction Conditions in the U.S. Economy - V. S. VASILIEV (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2018)
In the article the reasons for the deceleration of the average annual rates of economic growth of the United States are analyzed.  The rates declined in one and the half decade of the XXI century twice in comparison with the last three decades of the  twentieth century. Leading American economists and analysts  associated the main cause of the slowdown in economic growth with  a double drop in the rate of total factor productivity (TFP). This  indicator reflects the synergistic effects of the interaction of physical  and human capitals in the production process. The gradual decrease in the synergetic value of the interaction of labor and  capital in the US economy, other things being equal, also means a  decrease in the contribution of sinergetic factor to the rates of  economic growth and a greater priority in the state socio-economic policy of the capital factor in economic development. In  turn, the increasing role of capital in the economic development of  the US turns around with a sharp increase in inequality in income  distribution among different social strata of American society,  resulting in the bulk of the increase in economic production to  primarily 20% of the wealthiest layers of American society. The  growth of injustice in the distribution of goods and services in recent  decades in the United States was due to the lack of purposeful state  policy of the income redistribution. me. The absence of such a policy  stemmed from a growing crisis of most components of the  reproductive logistics of the American economy. In the end, general  conclusion is that the trend towards long-term decline in economic  growth will continue in the future because the US will be forced to invest trillions of dollars for infrastructure modernization in the  economy, which will not bring back quick economic returns in the short and possibly medium term.